2022
DOI: 10.3390/ijms231810746
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Soluble Amyloid Precursor Protein α (sAPPα) Levels by Acetylcholinesterase and Brain-Derived Neurotrophic Factor in Lung Cancer Cell Media

Abstract: In comparing two human lung cancer cells, we previously found lower levels of acetylcholinesterase (AChE) and intact amyloid-β40/42 (Aβ), and higher levels of mature brain-derived neurotrophic factor (mBDNF) in the media of H1299 cells as compared to A549 cell media. In this study, we hypothesized that the levels of soluble amyloid precursor protein α (sAPPα) are regulated by AChE and mBDNF in A549 and H1299 cell media. The levels of sAPPα were higher in the media of H1299 cells. Knockdown of AChE led to incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(50 citation statements)
references
References 92 publications
6
44
0
Order By: Relevance
“…As previously reported [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], 25 cm 2 tissue culture flasks were seeded with either human A549 (ATCC CCL-185) or H1299 (ATCC CRL-5803) NSCLC cells (ATCC, Manassas, VA, USA) in 5 mL of HyClone DMEM/F12 medium (GE Healthcare Life Sciences, Pittsburgh, PA, USA) supplemented with 10% Fetalgro BGS (RMBIO, Missoula, MT, USA) and 50 U/mL penicillin-streptomycin (Invitrogen Life Technologies, Carlsbad, CA, USA). Cells were grown overnight in an incubator set to 37 °C, 95% humidity, and 5% CO 2 .…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…As previously reported [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], 25 cm 2 tissue culture flasks were seeded with either human A549 (ATCC CCL-185) or H1299 (ATCC CRL-5803) NSCLC cells (ATCC, Manassas, VA, USA) in 5 mL of HyClone DMEM/F12 medium (GE Healthcare Life Sciences, Pittsburgh, PA, USA) supplemented with 10% Fetalgro BGS (RMBIO, Missoula, MT, USA) and 50 U/mL penicillin-streptomycin (Invitrogen Life Technologies, Carlsbad, CA, USA). Cells were grown overnight in an incubator set to 37 °C, 95% humidity, and 5% CO 2 .…”
Section: Methodssupporting
confidence: 75%
“…ELISAs were conducted, as we reported previously, using Nunc MaxiSorp 96-well Flat-Bottom plate (ThermoFisher) wells [ 50 , 51 , 54 , 57 , 60 ]. All absorbance measurements were in the linear range.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment with BDNF attenuated cisplatin-induced cell death and decreased the chemosensitivity of neuroblastoma cells to cisplatin, an effect that was blocked by cell treatment with the PI3K inhibitor, LY294002, suggesting a role of PI3K in BDNF’s rescue effects [ 41 ]. Our laboratory recently showed that treatment with acetylcholinesterase, well-known for its classical role in the catalytic hydrolysis of cholinergic neurotransmitters, shifted processing of the amyloid precursor protein away from the non-amyloidogenic pathway and toward the amyloidogenic pathway, whereas treatment with BDNF led to opposite effects [ 42 ]. While nicotine was earlier reported to regulate changes in the levels of BDNF that can affect nAChRs, and vice versa, in the brain from animal studies, relatively little is known about the interplay between nicotine and BDNF in NSCLC [ 38 , 39 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also reported minimal levels of AChE in H1299 cell media as compared to the media of A549 cells 36 and higher levels of mature brain-derived neurotrophic factor in the media of H1299 cells than in A549 cell media 37 . More recently, we showed that sAPPα levels are regulated by AChE and mBDNF and are higher in the media of H1299 cells compared to A549 cell media 38 .…”
Section: Introductionmentioning
confidence: 94%